Validation of a roadmap for mainstreaming nutrition-sensitive interventions at state level in Nigeria - Ezekannagha, O.; Drimie, S.; Fintel, D. von; Maziya-Dixon, Busie; Mbhenyane, X. (Springer, 2020)
Background National programs are often developed with little consideration to the sub-national local factors that might affect program success. These factors include political support, capacity for implementation of program and variation in malnutrition indices being tackled. State context factors are evident in the distribution of malnutrition (e.g. high prevalence or gap among Local Government Areas), in the implementation of nutrition-sensitive interventions (e.g. access to early childhood education) and in the political economic context (e.g. presence of external funding agencies). Context is shaped by the economy, population, religion, and poverty, which impact everyday lives. Considering these contexts, a roadmap was developed and validated. The aim of this paper is to report expert review and stakeholder validation to determine feasibility of the developed contextualised roadmap for two Nigerian states.